Integrating Total Quality Management into National Education Quality Assurance: A Conceptual Analysis of the Indonesian SPMP - Luthfiani Luthfiani; Widiastuti Widiastuti; Madhakomala Madhakomala (Journal of Social Work and Science Education, 2026)
This study aimed to examine the integration of Total Quality Management (TQM) principles and models within the framework of the Indonesian National Education Quality Assurance System (SPMP). The research employed a literature review methodology, analyzing related regulations, theoretical frameworks, and documented implementation strategies pertaining to TQM and the SPMP. The analysis indicates that TQM, including the PDCAE model and principles like stakeholder involvement and a customer-centered approach, has been formally adopted into the SPMP in Indonesian schools. However, its implementation has not been optimal, hindered by constraints such as limited funding, inadequate resources, and an unsupportive operational environment. Consequently, TQM integration remains largely theoretical and has not yet solidified into a pervasive, practical quality culture within the school system. To move beyond theoretical adoption, education policymakers and school administrators must prioritize securing adequate resources, building institutional capacity, and fostering an organizational environment that actively supports the practical application of TQM principles to establish a sustained quality culture. This study provides a structured analysis of the specific challenges in translating TQM theory into practice within Indonesia’s national education quality assurance framework. It contributes by highlighting the commonality of this theory-practice gap in developing countries and by clearly identifying the systemic barriers financial, resource-based, and cultural that impede the full realization of a TQM-based quality culture in schools.